The Activation and Reduction of N2 by Single/Double‐Atom Electrocatalysts: A First‐Principle Study. Issue 8 (19th February 2021) - Zhang, Shishi; Wang, Mingda; Jiang, Sheng; Wang, Hongming
Abstract: Developing low‐cost and highly efficient electrocatalysts for nitrogen reduction reaction (NRR) is one of the most attractive challenges. In this work, we systematically investigated the catalytic properties of the single atom catalysts (SAC) and the double atom catalysts (DAC) for NRR via First‐Principle calculations. The SAC and DAC were formed by single and double transition metal (TM) atoms anchored on N‐doped graphene monolayers (TMx N3x ‐graphene, x=1, 2; TM=Mo, Fe, Co, Ni and Cu). It is shown that both the SAC and the DAC have exhibited high catalytic properties for NRR. Moreover, when N2 is absorbed by its side‐on sites, SAC even performs better than DAC. And in five kinds of TM atoms, Fe‐complexes exhibit significantly improved catalytic properties. Especially, Fe1 N3 ‐graphene has the best catalytic activity for NRR with the lowest free energy change of 0.04 eV in the rate determining step (RDS). This work not only proposes the differences of SAC and DAC but also provides a new kind of single atom catalysts (SAC) for NNR. Abstract : The electrocatalytic activity of single atom catalysts (SAC) and double atom catalysts (DAC) for N2 ‐fixation is calculated and compared by a first‐principle study. Five transition metal atoms are chosen for studying the electronic effects. And different N2 adsorption mechanisms for SAC are investigated for comparing to DAC. It found that DAC does not always perform better catalytic properties than SAC.